2023
DOI: 10.1038/s42003-022-04388-4
|View full text |Cite
|
Sign up to set email alerts
|

A versatile Halo- and SNAP-tagged BMP/TGFβ receptor library for quantification of cell surface ligand binding

Abstract: TGFβs, BMPs and Activins regulate numerous developmental and homeostatic processes and signal through hetero-tetrameric receptor complexes composed of two types of serine/threonine kinase receptors. Each of the 33 different ligands possesses unique affinities towards specific receptor types. However, the lack of specific tools hampered simultaneous testing of ligand binding towards all BMP/TGFβ receptors. Here we present a N-terminally Halo- and SNAP-tagged TGFβ/BMP receptor library to visualize receptor compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…To investigate whether type II receptor domains that are implicated in human FOP pathology are conserved in medaka, we analyzed ligand binding domains (LBDs) by sequence comparison and performed a ligand surface binding assay (LSBA) [ 24 ] using fluorescently labelled hsActivin A-Cy5 ( Fig 5 , S6 Fig ). Sequence comparison of the hsACVR2A LBD with that of olaAcvr2ab highlighted subtle differences in two hydrophobic amino acids (Phe61 hsACVR2A / Tyr61 olaAcvr2ab, Ile83 hsACVR2A / Met83 olaAcvr2ab).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate whether type II receptor domains that are implicated in human FOP pathology are conserved in medaka, we analyzed ligand binding domains (LBDs) by sequence comparison and performed a ligand surface binding assay (LSBA) [ 24 ] using fluorescently labelled hsActivin A-Cy5 ( Fig 5 , S6 Fig ). Sequence comparison of the hsACVR2A LBD with that of olaAcvr2ab highlighted subtle differences in two hydrophobic amino acids (Phe61 hsACVR2A / Tyr61 olaAcvr2ab, Ile83 hsACVR2A / Met83 olaAcvr2ab).…”
Section: Resultsmentioning
confidence: 99%
“…Together, this suggests that Activin A binding to medaka olaAcvr2ab, olaAcvr2ba and olaAcvr2bb is likely to be similar as in the human counterparts. To test this hypothesis, we performed LSBA [ 24 ] using COS7-cells that transiently expressed Halo-tagged hsACVR2A, hsACVR2B, and olaAcvr2ab, olaAcvr2ba and olaAcvr2bb. As expected from previous studies, strong hsActivin A-Cy5 binding was observed for cells expressing hsACVR2A-Halo and hsACVR2B-Halo but not the non-binding receptor hsTGFBR2-Halo ( Fig 5B , S6B Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Activin A acts through its binding to activin type 2 receptors (ACVR2A or ACVR2B), which recruits type 1 receptors to form a receptor complex. [ 7 ] Then, intracellular signaling transductions are mediated by two pathways: the canonical pathway, where SMAD3 is phosphorylated and recruits SMAD4 to acquire transcriptional activity, and the noncanonical pathway, where subfamilies of the mitogen‐activated protein kinases including p38 activate downstream molecules. [ 8 ] SMAD3‐dependent signaling is indispensable for the proliferation of ovarian granulosa cells by activin A, and the downstream targets, Inha and Fst , feedback inhibits activin A‐mediated proliferation.…”
Section: Introductionmentioning
confidence: 99%